Intracellular respiratory dysfunction and cell injury in short-term anoxia of rabbit renal proximal tubules. - Takano, T (1985)
The effects of short-term anoxia and hypoxia were studied in a rabbit proximal renal tubule suspension in order to avoid the hemodynamic consequences of clamp-induced ischemia. The suspension was subjected to anoxia for 10-40 min and the effects on a number of cellular transport and respiratory parameters were monitored. Cellular respiration was measured upon addition of nystatin (Nys) to maximally stimulate Na pump activity. Mitochondrial respiration was measured in the tubules by addition of digitonin and ADP to obtain the state 3 respiratory rate. The release of lactate dehydrogenase (LDH) was measured as an index of plasma membrane damage. The cellular contents of K and Ca were also measured. Results show that 10 and 20 min of anoxia partially inhibited Nys-stimulated and mitochondrial respiration, and partially decreased the K contents, but all these effects were largely reversible after 20 min of reoxygenation. After 40 min of anoxia and 20 min of reoxygenation, all these variables remained irreversibly inhibited: Nys-stimulated respiration by 54%, mitochondrial respiration by 50%, K content by 42%, and LDH release was 40% of total. Ca content decreased slightly during anoxia, but increased up to fourfold during severe hypoxia; the excess Ca was released during the first 10 min of reoxygenation. The degree of respiratory impairment was identical during anoxia or hypoxia, suggesting that Ca accumulation was not associated with the impairment. Decreasing the extracellular Ca to 2.5 microM decreased LDH release significantly during anoxia, suggesting that plasma membrane damage during anoxia may be associated with increased intracellular free Ca. Addition of Mg-adenosine triphosphate during anoxia dramatically improved recovery of all the measured parameters after the anoxic period.